A systematic scoping review of microbial pathogens in ruminants with or without a history of abortions in Nigeria. - Kabiru Akinyemi; Samuel Ajoseh; Abdul-Azeez Anjorin; Wasiu Salami; Aminat Lawal; Marwa Bassiouny; Heinrich Neubauer; Gamal Wareth (German Journal of Veterinary Research)
Abortifacient pathogens such as bacterial [Brucella spp., Listeria spp., Leptospira interrogans ser., Coxiella burnetii, Campylobacter spp., Anaplasma spp., Chlamydia spp], mycotic [Aspergillus species and Candida species], protozoan [Toxoplasma gondii, Neospora spp.], and viral [Bluetongue virus (BTV), Schmallenberg virus (SBV), Bovine viral Diarrhea Virus (BVDV), and Peste des petits ruminants virus (PPRV)] pathogens are challenges for the productive and reproductive performance of ruminants (cattle, sheep, and goats) globally. No comprehensive report on epidemiology, associated risk factors, or economic burden of these infectious pathogens is available for Nigeria. This review estimated the distribution and burden of abortive pathogens in ruminants in Nigeria for the last twenty-two years (2000-2022). Research articles reporting the detection of any of the above-mentioned abortive pathogens in ready-to-slaughter ruminants (RTSR), sick ruminants (SR), and ruminants with abortive history (RWAH) in Nigeria were accessed using different repositories, including Google Scholar, Proquest, PubMed, ResearchGate and Scopus to determine the prevalence, spatial distribution, and associated risk factors. From a total of 140 articles selected for this review, eight bacterial, four viral, two parasitic, and two mycotic infectious agents were reported for Nigeria. This study reveals a prevalence of 28.2% viral agents, 14.43% bacterial pathogens, 14.24% protozoans, and 28.1% fungal agents in the reported tested samples. Brucellosis was the most often reported among bacterial diseases, followed by leptospirosis and listeriosis. Peste des petits ruminants virus infection was the most common viral disease, followed by bluetongue virus disease. Additionally, two parasitic diseases, neosporosis and toxoplasmosis, and two mycotic diseases, aspergillosis and candidiasis, were reported. In this study, stillbirth and abortion were recorded in 49.2% of sheep with PPRV, 58.95% in goats with Chlamydophila abortus and PPRV, and 6.4% in cattle with Brucella abortus and Histophilus somni infections. Lack of vaccines, open markets, and extensive husbandry systems were among the risk factors associated with different abortive pathogens. This study is a useful tool for researchers and government officers in risk assessment and management of livestock to improve livestock production in Nigeria.